(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
In order to prepare the sustained release tablet with levo-salbutamol sulphate we have used these excipients methylcellulose, PVPK30, magnesium stearate, talc, isopropyl alcohol, microcrystalline cellulose, lactose, HPMCK100, HPMCK4M. Here our approach was for making the sustained released matrix tablet by two ways, one is to make the tablet granules floating and the second one is by retarding the release of the levo-salbutamol sulphate from the matrix. We have already discussed the relationship with delaying the gastric transit time and the active drug absorption, if the tablet granules are floating in our introduction part. Since the above mentioned excipients are floating in nature so formulations with those excipients are supposed to be floating. We also showed a list of excipients those are used in the preparation of floating tablets. Now the second observation which was the release rate, among the three different formulations (mentioned in the introduction) we found different types of release. Since our objective is to prepare a sustained released tablet which will give a prolong release time, in that prospect two among the three formulations were disqualified (though we have not done the kinetic study). We observed desired effect in the formulation-2 during the preparation of experiment.